Resilience Management in Generation Z Entrepreneurs in Medan City - Pandiangan, Saut Maruli Tua; Dharmawan, Donny; Hariyanto, Mashudi; Pujiastuti, Endah; Zalogo, Erasma Fitilai (LPPPIPublishing, 2025)
The purpose of this study is to understand the extent to which resilience management influences the performance of generation Z entrepreneurs in Medan City. The type of research that is relevant to answer the questions in this study uses quantitative research. The sample used to represent the population in this study used a random sample of 50 respondents from generation Z entrepreneurs in Medan City. To answer the hypothesis in this study using multiple linear regression analysis. The research results show that pressure has a significant effect on the performance of generation Z entrepreneurs in Medan City. Risk has a significant effect on the performance of generation Z entrepreneurs in Medan City.